Characterization of cxorf21 Provides Molecular Insight Into Female-Bias Immune Response in SLE Pathogenesis - Harris, Valerie M.; Koelsch, Kristi A.; Kurien, Biji T.; Harley, Isaac T. W.; Wren, Jonathan D.; Harley, John B.; Scofield, R. Hal (Frontiers in Immunology, 2019)
Background: Ninety percent of systemic lupus erythematosus (SLE) patients are women. X chromosome-dosage increases susceptibility to SLE and primary Sjögren’s Syndrome (pSS). Chromosome X open reading frame 21 (CXorf21) escapes X-inactivation and is an SLE risk gene of previously unknown function. We undertook the present study to delineate the function of CXorf21 in the immune system as well as investigate a potential role in the sex bias of SLE and pSS. Methods: Western blot protein analysis, qPCR, BioPlex cytokine immunoassay, pHrodo™ assays, as well as in vitro CRISPR-Cas9 knockdown experiments were employed to delineate the role of CXorf21 in relevant immunocytes. Results: Expressed in monocytes and B cells, CXorf21 basal mRNA and protein expression levels are elevated in female primary monocytes, B cells, and EBV-transformed B cells compared to male cells. We also found CXorf21 mRNA and protein expression is higher in both male and female cells from SLE patients compared to control subjects. TLR7 ligation increased CXorf21 protein expression and CXorf21 knockdown abrogated TLR7-driven increased IFNA1 mRNA expression, and reduced secretion of both TNF-alpha and IL-6 in healthy female monocytes. Similarly, we found increased pH in the lysosomes of CXorf21-deficient female monocytes. Conclusion: CXorf21 is more highly expressed in female compared to male cells and is involved in a sexually dimorphic response to TLR7 activation. In addition, CXorf21 expression regulates lysosomal pH in a sexually dimorphic manner. Thus, sexually dimorphic expression of CXorf21 skews cellular immune responses in manner consistent with expected properties of a mediator of the X chromosome dose risk in SLE and pSS.